Advocacy for Sharia and Legal Equality in Indonesia: An Examination of the Competency of Sharia Advocates in Banyumas - Maula, Bani Syarif; Nada, Syifaun (Transformatif, 2024)
Sharia advocates (Sharia lawyers) in Indonesia face the challenge of maintaining their significant role amidst the dominance of general advocates. This research evaluates the professionalism of Sharia advocates in the Banyumas region, focusing on the Banyumas Religious Court, Banyumas District Court, Purwokerto Religious Court, and Purwokerto District Court. This study used a qualitative and constructivist approach and collected primary data through interviews with Sharia advocates and secondary data from documents. Findings indicate that legislation recognizes Sharia advocates as professional advocates eligible to practice in all courts, akin to general advocates. However, Islamic universities, especially Sharia faculties, need to prepare graduates to compete with general law graduates for advocacy roles. In the Banyumas region, Sharia advocates provide legal services primarily in civil law cases under religious court jurisdiction across four courts. The main challenge for Sharia advocates is the public perception that they only handle Islamic legal cases and only practice in religious courts. Furthermore, there is a strong negative stigma among legal practitioners regarding the low proficiency of Sharia advocates in positive law, leading to their limited involvement in handling cases in District Courts (Civil Courts).